Lupane-Type Triterpenoidal Saponins from Pulsatilla chinensis and Their Anticomplement Activities through the Classical Pathway - Xu, Qiong-ming; Shu, Zhan; Zhu, Wei-feng; Liu, Yan-li; Li, Xiao-ran; Yang, Shi-lin (Planta Medica, 2013)
Four (1–4) previously unknown lupane-type triterpenoidal saponins were isolated from the roots of Pulsatilla chinensis, along with six triterpene saponins (5–10). The structures of saponins 1–4 were determined as 23-hydroxy-3β-[(O-β-D-glucopyranosyl-(1 → 4)-α-L-arabinopyranosyl)]lup-20(29)-en-28-oic-acid 28-O-β-D-glucopyranosyl-(1 → 6)-β-D-glucopyranosyl ester (1), 23-hydroxy-3β-[(O-α-L-rhamnopyranosyl-(1 → 2)-[β-D-glucopyranosyl-(1 → 4)]-α-L-arabinopyranosyl)]lup-20(29)-en-28-oic-acid 28-O-β-D-glucopyranosyl-(1 → 6)-β-D-glucopyranosyl ester (2), 3β-[(O-β-D-glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl)]lup-20(29)-en-28-oic-acid 28-O-β-D-glucopyranosyl-(1 → 6)-β-D-glucopyranosyl ester (3), and 3β-[(O-β-D-glucopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl)]lup-20(29)-en-28-oic-acid 28-O-α-L-rhamnopyranosyl-(1 → 4)-β-D-glucopyranosyl-(1 → 6)-β-D-glucopyranosyl ester (4), on the basis of hydrolysis and spectral evidence, including 1D- and 2D-NMR and HR-ESI-MS analyses. These pure isolates (1–10) were tested for their anticomplement activity, using an in vitro assay of the complement system of the classical pathway.
Keywords: Pulsatilla chinensis; Ranunculaceae; triterpenoidal saponins; lupine; anti-complementary activity; classical pathway